Highly Sensitive and Selective Hydrogen Gas Sensor Using the Mesoporous SnO2 Modified Layers - Niuzi Xue (Sensors, 2017)
It is important to improve the sensitivities and selectivities of metal oxide semiconductor (MOS) gas sensors when they are used to monitor the state of hydrogen in aerospace industry and electronic field. In this paper, the ordered mesoporous SnO2 (m-SnO2) powders were prepared by sol-gel method, and the morphology and structure were characterized by X-ray diffraction analysis (XRD), transmission electron microscope (TEM) and Brunauer–Emmett–Teller (BET). The gas sensors were fabricated using m-SnO2 as the modified layers on the surface of commercial SnO2 (c-SnO2) by screen printing technology, and tested for gas sensing towards ethanol, benzene and hydrogen with operating temperatures ranging from 200 °C to 400 °C. Higher sensitivity was achieved by using the modified m-SnO2 layers on the c-SnO2 gas sensor, and it was found that the S(c/m2) sensor exhibited the highest response (Ra/Rg = 22.2) to 1000 ppm hydrogen at 400 °C. In this paper, the mechanism of the sensitivity and selectivity improvement of the gas sensors is also discussed.